hii all...I need to answer this question urgently.

The covariance can be expressed in the following formula:-

Cov(x,y) = ∑ (x-E(x)) (y-E(y)

If we have two new variables. U=aX + b and V = cY+d where a, b, c and d are arbitrary constants.

then Cov (x,y) = ac Cov(x,y) , the proof of this is below.

Cov(aX + b, cY + d) = E([aX + b − E(aX + b)][cY + d − E(cY + d)])

= E([aX + b − aE(X) − b][cY + d − cE(Y ) − d])

= E(a[X − E(X)]c[Y − E(Y )])

= acE([X − E(X)][Y − E(Y )])

= acCov(X, Y )

the Question is what does the above result (Cov (x,y) = ac Cov(x,y) ) mean?

I hope that someone here can tell me the answer.